2000
DOI: 10.1111/j.1549-8719.2000.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Histamine‐Induced Endothelial Permeability Responses after Pacing‐Induced Heart Failure: Role for Endogenous Catecholamines

Abstract: We conclude that endogenous catecholamines, acting via beta 2-adrenergic receptors, attenuate the permeability response to histamine in pacing-induced heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The β-adrenergic (β-ARs) agonists are capable of modulating the two distinct components of keratinocyte directional migration via divergent signaling pathways: 1) migration rate via a cAMP-independent, mitogenactivated-protein-kinase-dependent pathway [57] and 2) galvanotaxis by a cAMP-dependent one. Previous data have shown that both endogenous and exogenous catecholamines act to attenuate the permeability response to various inflammatory mediators via β1- [58] and β2adrenoceptors [59] [60] [61] [62]. Additionally, because β-adrenergic agonists and antagonists modulate both keratinocyte migration and galvanotaxis, they could be valuable tools for controlling reepithelialization and restoration of barrier function, an essential component of the wound healing process.…”
Section: Skin's Beta2 Adrenergic Receptors (β-Ars)mentioning
confidence: 99%
“…The β-adrenergic (β-ARs) agonists are capable of modulating the two distinct components of keratinocyte directional migration via divergent signaling pathways: 1) migration rate via a cAMP-independent, mitogenactivated-protein-kinase-dependent pathway [57] and 2) galvanotaxis by a cAMP-dependent one. Previous data have shown that both endogenous and exogenous catecholamines act to attenuate the permeability response to various inflammatory mediators via β1- [58] and β2adrenoceptors [59] [60] [61] [62]. Additionally, because β-adrenergic agonists and antagonists modulate both keratinocyte migration and galvanotaxis, they could be valuable tools for controlling reepithelialization and restoration of barrier function, an essential component of the wound healing process.…”
Section: Skin's Beta2 Adrenergic Receptors (β-Ars)mentioning
confidence: 99%